Stability and recovery of cyclodextrin encapsulated catechin in various food matrices. (1st March 2019) - Ho, Siyin; Thoo, Yin Yin; Young, David James; Siow, Lee Fong
Highlights: IC and free catechin was more stable in a solid matric. IC in milk and yogurt showed the highest percentage recovery of catechin. Semi-solid matrix (yogurt) was the most suitable matrix. Inclusion complex of catechin with β-CD masked the bitterness of catechin. Abstract: Catechin is astringent in taste, sparingly soluble in water and sensitive to oxygen, light and pH. These properties restrict its application in food products. The present study investigated the stability of inclusion complex (IC) and catechin in various food matrices and investigated in vitro recovery profile of catechin and IC in liquid, semi-solid and solid food matrices. Besides, the sensory profile of IC added yogurt was also determined. Results showed that IC and catechin was more stable in solid matrix compared to semi-solid and liquid matrices. IC added in milk and yogurt show the highest percentage recovery of catechin compared to IC added in cheese and catechin added in all the matrices in in vitro digestive system. Through IC, β-CD masked the bitterness of catechin. These results suggest that protection of antioxidant such as catechin by β-CD inclusion complex may have applications in functional foods and health supplements.